Memory of men about living with alcohol consumption (Research, Society and Development, 2020)
Introduction: In the Brazilian context, significant and progressive consumption of alcohol and other drugs is observed in all social classes, this practice is considered one of the main factors that affect the health of the population. Thus, the aim of this study is to understand the meaning of men's memory about living with habitual alcohol consumption. Method: Qualitative, exploratory study, based on thematic oral history. Six alcoholic men residing in the interior of Bahia collaborated with the study, four users of a Psychosocial Care Center for alcohol and other drugs and two residents in a peripheral community, served by a Family Health Strategy team. The memories were evoked using the semi-structured interview technique between April and June 2019. The content of the oral reports was analyzed using the content analysis technique. Results: Employees referred to habitual alcohol consumption as a consolidated process throughout life, started, early, in childhood and adolescence, until it became addictive. In adulthood, negative impacts were noticeable in family dynamics, in the world of work, in finances, in behavior, in the perception of others and in self-perception. The life trajectory with alcohol resulted in an old age devoid of projects and without family ties. Conclusions: Taking the oral reports of alcoholic men participating in this study as a starting point, the meanings attributed to alcoholism were associated with interpersonal relationships, traversing a trajectory of family and social inclusion, exclusion and ambiguous feelings of contentment, suffering.